ACTUAL LEARNING TRAJECTORY SISWA PADA PEMBELAJARAN ETNOMATEMATIKA BERBASIS PERMAINAN LAYANG-LAYANG DALAM KONSEP GEOMETRI KELAS IV - Lilis Selviana Dewi; Dindin Abdul Muiz Lidinillah; Pidi Mohamad Setiadi (STKIP Subang, 2026)
Geometry learning in elementary schools remains challenging due to the abstract nature of geometric concepts, making it difficult for students to develop meaningful conceptual understanding. One approach to addressing this issue is integrating cultural contexts into mathematics instruction through ethnomathematics, enabling students to relate mathematical concepts to their everyday experiences. This study aimed to describe the students' Actual Learning Trajectory in ethnomathematics-based learning using the traditional kite game to support the understanding of geometry concepts in fourth-grade elementary students. The study employed the Educational Design Research (EDR) approach involving 25 fourth-grade students from an elementary school in Tasikmalaya. Data were collected through classroom observations, interviews, documentation, and students' work, and were analyzed descriptively to identify the learning trajectory that emerged during the instructional process. The findings revealed that the students' actual learning trajectory developed progressively, beginning with recognizing the traditional kite game as a cultural context, identifying geometric elements of the kite, exploring the properties of plane figures, and finally relating geometric concepts to real-life experiences. The ethnomathematics-based learning approach provided a more contextual learning experience, promoted students' active participation, and facilitated a more concrete understanding of geometry concepts. These findings indicate that the traditional kite game serves as an effective cultural context for developing students' learning trajectories in elementary geometry learning.